What does the digital student want? - Pisanski Peterlin, Agnes (ELOPE (Ljubljana), 2015)
New online educational tools have opened new possibilities for cross-cultural collaboration which supports critical thinking and encourages learner autonomy. Nevertheless, the success of a crosscultural collaborative experience cannot be taken for granted, since it inevitably involves the need to bridge transcultural differences. This paper presents an American-Slovene cross-cultural collaborative project with a focus on the perceptions of the Slovene student-participants. In particular, it examines their views of one of the components of the collaborative project, specifically, the collaborative wiki writing assignment, introduced to develop the students' academic literacy skills. The findings of the questionnaire study show that the participants' experiences with the cross-cultural collaboration were positive, although their answers reveal a slight preference for less challenging activities. Nevertheless, even the fairly demanding writing assignment was generally perceived to be interesting and useful: while its full interactive potential was not realized due to the participants' reluctance to engage in editing, the wiki is clearly an efficient tool for promoting academic literacy.
Keywords: medkulturno sodelovanje; razvoj akademske pismenosti; spletna orodja za izobraževanje; wiki